2017
DOI: 10.1017/s0025315417000492
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation between Mediterranean and Atlantic populations of the common prawn Palaemon serratus (Crustacea: Palaemonidae) reveals uncommon phylogeographic break

Abstract: The Atlantic–Mediterranean transition zone between the Alborán Sea and the Gulf of Cádiz constitutes the most prominent marine geographic barrier in European waters and includes known phylogeographic breaks such as the Strait of Gibraltar and the Almería-Oran Front. A genetic shift in this area has been previously documented for the European littoral shrimp Palaemon elegans. Here we carried out a phylogeographic analysis with the congeneric and sympatric species Palaemon serratus to test for similar intraspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Localities from the south of the Iberian Peninsula were genetically closer to Mallorca than to the other Atlantic localities. These results were similar to those obtained by Weiss et al () for P. serratus analysing one nuclear and two mitochondrial genes, or in Pagurus excavatus , Pagurus alatus , Plesionika heterocarpus , Parapenaeus longirostris and Munida intermedia from a mitochondrial gene analysis (García‐Merchán et al, ). The surface circulation in the Gulf of Cadiz by the Eastern North Atlantic Central Waters (ENACW) from the Portuguese Coastal Transition Zone and the Azores Current (Sánchez & Relvas, ) might allow larval transport towards the Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Localities from the south of the Iberian Peninsula were genetically closer to Mallorca than to the other Atlantic localities. These results were similar to those obtained by Weiss et al () for P. serratus analysing one nuclear and two mitochondrial genes, or in Pagurus excavatus , Pagurus alatus , Plesionika heterocarpus , Parapenaeus longirostris and Munida intermedia from a mitochondrial gene analysis (García‐Merchán et al, ). The surface circulation in the Gulf of Cadiz by the Eastern North Atlantic Central Waters (ENACW) from the Portuguese Coastal Transition Zone and the Azores Current (Sánchez & Relvas, ) might allow larval transport towards the Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 90%
“…Weiss et al () suggested that specimens of the Guadalquivir estuary form a very homogeneous Mediterranean population probably because of a founder effect; that is, a new population founded by only a few individuals and therefore with low genetic variety. Furthermore, as Weiss et al () has already pointed out, and as indicated in the present study, isolation was detected in the Guadalquivir estuary. The results showed that, despite their close geographic proximity, both Conil and Gibraltar were not connected with Guadalquivir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, it is known that population connectivity across the Atlantic-Mediterranean transition is reduced in other species by different oceanographic discontinuities, namely the Strait of Gibraltar 24,44 , the Balearic Front and the Ibiza Channel 45,46 . Most recently, in the congeneric common littoral shrimp Palaemon serratus, both mtDNA 47 and nuclear 25 markers have reported strong genetic differentiation among Atlantic and Mediterranean localities with an unusual phylogeographical break located west of the Strait of Gibraltar in the Gulf of Cádiz.…”
Section: Discussionmentioning
confidence: 99%
“…Although the estimates involving the Mediterranean sample of P. serratus must be taken carefully, as only three PCG fragments could be recovered, previous population genetics analyses would support the consideration of these two populations as separated species. Strong genetic differentiation between Atlantic and Mediterranean localities was detected along the geographical distribution range of P. serratus using two mitochondrial and one nuclear PCG [87] and 17 microsatellite markers [88]. Two geographic lineages were identified in P. serratus with an unusual phylogeographical break located west of the Strait of Gibraltar in the Gulf of Cádiz.…”
Section: Plos Onementioning
confidence: 95%